PENERAPAN MEDIA PEMBELAJARAN CROSSWORD PUZZLE (TEKA-TEKI SILANG) UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS VII MATA PELAJARAN PPKN DI SMP NEGERI 1 BATU - Dessy Herawati; Mohamad Syahri (Institute Agama Islam Al-Qolam Malang, 2023)
The learning process for Pancasila Education is currently still carried out using the convensional method. This causes boredom in students when the teaching and learning process takes place. The purpose of this study is to describe the application of crossword puzzle game media, and to determine the effect of student learning activeness using crossword puzzle game media. This study used a Classroom Action Research design. Implementation of this class action using two cycles. The results showed that in the first cycle students were still lacking in responding and being active in the learning process. The average activeness of class VII students is 50.98% and is included in the medium criteria. Several changes were made in cycle II. The results showed an increase in cycle II. The average class VIII student activity is 75.5%. This percentage can be categorized in the high criteria.